2020
DOI: 10.2355/isijinternational.isijint-2019-734
|View full text |Cite
|
Sign up to set email alerts
|

Influence of H<sub>2</sub>–H<sub>2</sub>O Content on the Reduction of Acid Iron Ore Pellets in a CO–CO<sub>2</sub>–N<sub>2</sub> Reducing Atmosphere

Abstract: Using hydrogen as a reducing agent for iron production has been the focus of several studies due to its environmental potential. The aim of this work is to study the influence of H 2-H 2 O content in the gas phase on the reduction of acid iron ore pellets under simulated blast furnace conditions. Temperature and gas compositions for the experiments were determined with multi-point vertical probes in an industrial blast furnace. The results of the reduction tests show that higher temperatures and H 2 content in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 16 publications
5
20
0
Order By: Relevance
“…This indicates the importance of choosing the right ratio of H 2 /CO and not simply raising the amount of hydrogen content [33]. Abdelrahim et al, found that the pellets reduced in CO-CO 2 -H 2 -H 2 O-N 2 have more porosity and surface area than that reduced in CO-CO 2 -N 2 [34]. Formation of carbide, slower reduction, and reaching the complete reduction at higher temperatures, for the hematite reduction by CO in comparison with H 2 was reported by Abu Tahari et al [35].…”
Section: Effect Of H2/co Ratiomentioning
confidence: 99%
“…This indicates the importance of choosing the right ratio of H 2 /CO and not simply raising the amount of hydrogen content [33]. Abdelrahim et al, found that the pellets reduced in CO-CO 2 -H 2 -H 2 O-N 2 have more porosity and surface area than that reduced in CO-CO 2 -N 2 [34]. Formation of carbide, slower reduction, and reaching the complete reduction at higher temperatures, for the hematite reduction by CO in comparison with H 2 was reported by Abu Tahari et al [35].…”
Section: Effect Of H2/co Ratiomentioning
confidence: 99%
“…Elevated amounts of hydrogen also affect the reduction of the iron bearing layers in the furnace. [ 25 ] Thus, further research on the topic of hydrogen and water vapor in BF is important.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the behavior of the produced briquettes under high-temperature resembling conditions in a BF, a modified blast furnace simulator (BFS) was used. The schematic diagram of the BFS, which was used in our previous work to study pellet reduction [44], is shown in Fig. 1.…”
Section: Blast Furnace Simulator High-temperature Behaviormentioning
confidence: 99%